KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DALAM MENYELESAIKAN SOAL CERITA DITINJAU DARI KEMAMPUAN LITERASI NUMERASI KELAS VIII MTs. NW BAGIK POLAK TAHUN AJARAN 2023/2024 - Hindayani, Zuwiya; Nyoman Sridana; Nani Kurniati; Laila Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT The purpose this study is to describe the ability solve mathematical problems in solving story problems based on the numeracy literacy skills of grade VIII MTs.NW Bagik Polak for 2023/2024 academic year. The research method used is descriptive qualitative. The study subjects were 6 people of 20 students with two students each having high, medium and low numeracy literacy skills. The instruments used in this research numeracy literacy tests with multiple-choice question types and mathematical problem solving ability tests with description question types. Analysis technique used is examine the results student work based on indicators set in numeracy literacy ability and supported by work results mathematical problem solving ability based on predetermined indicators. The results showed that subjects with high numeracy literacy skills had high mathematical problem solving abilities, because they could solve story problems according to steps and meet almost all mathematical problem solving indicators. Subjects with moderate numeracy literacy skills have quite good mathematical problem solving skills because they can meet several mathematical problem solving indiactors namely understanding problems and implementing strategies, but in implementing strategies are still not appropriate because the subjects have not been able to plan appropriate problem solving. Subjects low numeracy literacy skills have low mathematical problem solving skills, because subjects cannot solve story problems according to mathematical problem solving steps and only able to meet the indicators of implementing strategy but still not right because students cannot understand the problem well and plan problem solving so that the solution obtained is not right.